(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims through these two standards to determine the necessary bases for reporting useful information to users of the final accounts about the nature, type, amount and timing of revenues, and that the (IPSAS 9) and (IPSAS 23) standards will have a significant impact on revenue auditing procedures internationally and locally and its impact on the work of the external auditor by understanding their requirements and working to find completely new procedures that help him audit revenues in accordance with international accounting standards in the public sector. In addition, the revenue audit program approved by the Federal Board of Supreme Audit is limited and the General Authority of Customs, when applying the accrual basis, must have a revenue audit program that is familiar with all aspects related to maximizing revenues. A revenue audit program was proposed in the practical aspect in the third section to be applied to the General Authority of Customs. The researchers reached a set of conclusions, the most prominent of which is that the application of international accounting standards in the public sector in the General Authority of Customs requires an audit program, and that the audit procedures approved by the Federal Financial Supervision Bureau do not meet the requirements as they pertain to institutions applying the cash basis. Accordingly, the researchers proposed several recommendations, the most important of which is relying on international accounting standards in the public sector, Standard (IPSAS 9) and Standard (IPSAS 23), and relying on the proposed audit procedures when auditing the revenues collected by the General Authority of Customs.